Determinan Pengungkapan Akuntansi Sumber Daya Manusia (Pada Perusahaan Manufaktur di Bursa Efek Indonesia) - Bella Herliza; Siti Nurhayati Nafsiah (JURNAL ILMIAH EDUNOMIKA, 2024)
Human resources (HR) play a crucial role as drivers in all corporate activities. Competent HR bring competitive advantages and add value. Human resource accounting is the process of identifying, measuring, and communicating HR data to various stakeholders. HR is considered a valuable asset to companies, as the company's vision and strategies would not succeed without quality HR. This research focuses on the manufacturing industry in the Indonesia Stock Exchange (IDX), exploring the factors influencing human resource accounting disclosure. The identified population consists of 102 manufacturing companies in the basic and chemical industry sectors listed on the IDX in 2022. The sampling method used is purposive sampling based on considerations that yield a sample of 80 manufacturing companies in the basic and chemical industry sectors. Secondary data used in this study is from the annual reports of the year 2022. Additionally, secondary data is obtained from various company websites, articles, books, and previous research as sources. In this study, the dependent variable is human resource accounting disclosure, while the independent variables are profitability, company size, institutional ownership, product diversification, and share concentration. The research findings indicate that overall, all independent variables have a significant positive influence on human resource accounting disclosure. However, when analyzed separately, variables such as profitability, product diversification, share ownership concentration, and institutional ownership do not have a significant influence on human resource accounting disclosure in manufacturing companies listed on the IDX. Only the variable of company size has a significant influence on human resource accounting disclosure. Keywords: accounting disclosure, HR accounting, human resources (HR), manufacturing industry